Synaptic Activity and Bioenergy Homeostasis: Implications in Brain Trauma and Neurodegenerative Diseases - Khatri, Natasha; Man, Hengye (Frontiers in Neurology, 2013)
Powered by glucose metabolism, the brain is the most energy-demanding organ in our body. Adequate ATP production and regulation of the metabolic processes are essential for the maintenance of synaptic transmission and neuronal function. Glutamatergic synaptic activity utilizes the largest portion of bioenergy for synaptic events including neurotransmitter synthesis, vesicle recycling, and most importantly, the postsynaptic activities leading to channel activation and rebalancing of ionic gradients. Bioenergy homeostasis is coupled with synaptic function via activities of the sodium pumps, glutamate transporters, glucose transport, and mitochondria translocation. Energy insufficiency is sensed by the AMP-activated protein kinase (AMPK), a master metabolic regulator that stimulates the catalytic process to enhance energy production. A decline in energy supply and a disruption in bioenergy homeostasis play a critical role in multiple neuropathological conditions including ischemia, stroke, and neurodegenerative diseases including Alzheimer’s disease and traumatic brain injuries.